The future envelope 1 a multidisciplinary approach - Knaack, Ulrich (IOS Press, 2013)
"Facades convey the image of new architecture. Today the planning of this very complex building component requires a collaboration of many specialists. A multitude of possibilities are being projected into the building envelope. Design, visionary construction, new materials, the desire to achieve optimum energy performance or even energy generation all meet with predominantly conventional crafts. Experts from the fields of architecture, structural and climate design, material science, construction and product development, industry, planning and building innovations will reflect on current projects and their vision for the future."--Jacket